2014
DOI: 10.1007/s00221-014-4048-0
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific stability in muscle activation space during unintentional movements

Abstract: We used robot-generated perturbations applied during position-holding tasks to explore stability of induced unintentional movements in a multi-dimensional space of muscle activations. Healthy subjects held the handle of a robot against a constant bias force and were instructed not to interfere with hand movements produced by changes in the external force. Transient force changes were applied leading to handle displacement away from the initial position and then back towards the initial position. Inter-trial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Note that F PERT increased smoothly over 0.5 s to avoid inducing so-called triggered responses (Hammond 1954; Tatton et al 1978; reviewed in Shemmel et al 2010). A recent study of the electromyographic patterns in arm muscles using similar perturbations (Falaki et al 2014) has shown no visible phasic muscle reactions that would resemble triggered responses.…”
Section: Methodsmentioning
confidence: 99%
“…Note that F PERT increased smoothly over 0.5 s to avoid inducing so-called triggered responses (Hammond 1954; Tatton et al 1978; reviewed in Shemmel et al 2010). A recent study of the electromyographic patterns in arm muscles using similar perturbations (Falaki et al 2014) has shown no visible phasic muscle reactions that would resemble triggered responses.…”
Section: Methodsmentioning
confidence: 99%
“…ΔM and ΔCOP AP data were computed from IEMG norm and integrated COP AP (within 50-ms time windows) data from the body sway task. Both ΔM and ΔCOP AP , were filtered with a 5 Hz, low-pass, 4th order, zero-lag Butterworth filter (Falaki et al 2014, 2016). Multiple regression analysis was performed for each subject separately: ΔitalicCOPAP=k1ΔM1+k2ΔM2+k3ΔM3+k4ΔM4…”
Section: Methodsmentioning
confidence: 99%
“…F PERT increased smoothly over 0.5 s to avoid triggered (pre-programmed, long-loop reflex) responses (Hammond 1954; Tatton et al 1978; Shemmel et al 2010). In an earlier study, similar perturbations showed no visible phasic muscle reactions (Falaki et al 2014). During the final phase, Recovery , the robot force returned to F BIAS , also over 0.5 s.…”
Section: Methodsmentioning
confidence: 70%
“…In an earlier study, we recorded arm muscle electromyographic signals (EMGs) using surface electrodes in a somewhat similar setup (Falaki et al 2014). In that study, the pilot analysis of EMG changes during the dwell time was disappointing: The EMG signals were relatively low (note that the external forces used in both studies were not very high to avoid fatigue), and we could not detect their consistent changes over the dwell time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation